A set of exercises hopping pattern for the initial diagnosis of the degree of overtraining syndrome in athletes involved in cyclic sports - Olga Peshkova (Слобожанський науково-спортивний вісник, 2015)
In the article the author presents data on the method of diagnosis of the initial degree of overtraining syndrome in athletes involved in cyclic sports. Purpose: to develop and assess diagnostic tests to detect early signs of overtraining syndrome in athletes involved in cyclic sports. Material and Methods: developed by the author was applied a set of jumping exercises in 42 athletes with an initial degree of overtraining syndrome in age from 21 to 27 years old male, who were engaged in cyclic kinds of sports (athletics, skiing, cycling, swimming). To control the data obtained were compared with the same athletes before their clinical and functional signs of overtraining syndrome were identified. Results: using the jumping exercises on track kinematometra control and the expectation of landing an athlete with a spade to the side, front and rear walls of the rectangular contour of the rotation at the time of jumping on 90o and without it as a set of available physical exercise greatly simplifies the identification of the main indicators characterizing changes in the central nervous system in the early stages of overtraining syndrome